The effect of synthetic 4A and 5A zeolite-based nitrogen capture systems on diesel engine performance and emissions - Hazar, Hanbey; Firat, Selahattin Ozgur; Sevinc, Huseyin (Pergamon-Elsevier Science Ltd, 2026)
In the study, a filtration system was designed using pressure swing adsorption (PSA) technique and synthetic zeolites and its effects on exhaust emissions and performance attributes of a diesel engine were investigated by integrating this system into the intake line. Synthetic 4A and 5A zeolites were used as adsorbent materials in the PSA unit. Tests were conducted on a single cylinder diesel engine operated at constant speed under variable load conditions. SEM and EDX analyses were performed to characterize the surface properties of the zeolites. According to the oxygen measurements obtained at the outlet of the filtration system, the 4A and 5A zeolites provided an air outlet containing oxygen at the rate of 25.8% and 27.36%, respectively. The most remarkable improvements in exhaust emissions and performance parameters were obtained with the 5A zeolite. The use of 5A resulted in reductions in carbon monoxide, hydrocarbon, smoke density, and brake-specific fuel consumption by 17.31%, 13.83%, 17.42%, and 4.18%, respectively. Conversely, nitrogen oxides, brake thermal efficiency, exhaust gas temperature, torque, engine noise and vibration increased by 15.37%, 4.61%, 7.04%, 4.42%, 1.4%, and 3.1%, respectively. In-cylinder peak pressure also increased by 5.33% with PSA. This study provides the first experimental integration of a PSA-based continuous oxygen-enrichment system using synthetic 4A and 5A zeolites into a diesel engine, demonstrating how zeolite type and microstructure influence oxygen concentration and combustion behaviour. The findings show that continuous on-board oxygen enrichment can enhance diesel engine performance while reducing most exhaust emissions.
Keywords: Diesel engine; Exhaust emissions; Performance; Synthetic zeolites; Oxygen enrichment